中国国有企业融资结构与行为分析 = The capital structure and financing behavior of state-owned enterprises in China - 李建阳 Li, Jianyang (2010)
截至目前，对高债务和国有企业在中国，它始于1980年代中期，并从那时以来不断恶化的高风险的资本结构问题的研究，基本上采取两种方法。一个属性，如高杠杆的国有企业管理不善，而其他认为，在政治压力下高银行贷款和中央政府向这些企业提供资金帮助高杠杆勉强。但是这两种方法不能给我们有关这些企业资本结构的严重问题的全部图片。 Up to now, research on the problems of high-debt and high-risk capital structures of state-owned enterprises in China, which started from mid-1980s and has been deteriorating since then, adopted basically two approaches. One attributes such high leverage to the poor management of state-owned enterprises, while the other argues that high bank lending under political pressure and the reluctance of the central government in providing fund to these enterprises contribute to the high leverage. But the two approaches cannot give us the full pictures of the serious problems relating to capital structures of these enterprises.